A Change in the Indeks of Retained Strength in the AC-WC Mixture with the Additional Waste Rubber from Used Tires (Crumb Rubber) - Hidayat, Kurniawan; Pristyawati, Tantin; Safarizki, Hendramawat Aski (JMPM (Jurnal Material dan Proses Manufaktur), 2023)
The growth of the number of motorized vehicles in Indonesia every year always increases. The consequence of the growth in the number of motorized vehicles is the increasing production of motorized vehicle tires which results in the accumulation of used tire waste. One of the innovations to reduce the waste of used tire rubber is to use it in asphalt mixtures. The study was conducted to determine the change in the index of retained strength in the Asphalt Concrete – Wearing Coarse (AC-WC), is the top layer of pavement which functions as the wear layer,  mixture with the addition of waste rubber from used tires (crumb rubber) meeting the Bina Marga Specifications. The results showed that the addition of waste rubber tires affected the marshall characteristics, namely, the highest specific gravity, density, Voids Filled With Asphalt (VFA), and stability values were at a level of 1%, while the highest values of Voids in Mix (VIM), Void in Mineral Agregate (VMA), and flow were at a level of 9%. From the index of retained strength test, it shows that water affects the durability of the AC-WC mixture, as evidenced by the highest value at the duration of immersion for 24 hours with a concentration of 1%, which de-creases with increasing duration of immersion. The addition of used tire rubber waste (crumb rubber) to the AC-WC mixture has met the Bina Marga Specifications on the Marshall characteristics test, but the change in the index of retained strength was only for a 24-hour immersion duration, while for other durations were not according the Bina Marga Specifications.